A Survey of Patient-Relevant Outcomes in Pediatric Craniopharyngioma: Focus on Hypothalamic Obesity - Craven, Meghan; Crowley, Julia H.; Chiang, Lucas; Kline, Cassie; Malbari, Fatema; Hocking, Matthew C.; McCormack, Shana E. (Frontiers in Endocrinology, 2022)
Context: Individuals treated for pediatric craniopharyngioma, a rare, grade 1 brain tumor, frequently develop hypothalamic obesity, a complication often recalcitrant to intervention. Although hypothalamic obesity is known to adversely impact quality of life, less is known about how caregivers and patients experience this condition. Objective: Our goal was to examine the approaches that families take towards weight management and the impact on social function in individuals with craniopharyngioma and obesity. Individuals with craniopharyngioma without obesity were included as a comparison. Subjects and Methods: Adult caregivers of children <18y with craniopharyngioma completed a web-based survey posted by a patient advocacy organization between February and July 2020. Questions related to the child’s diagnosis, medications, lifestyle modifications, and social function along with research priorities. Descriptive statistics were generated. Linear regression was used to assess the independent effects of obesity and other covariates on social function. Results: Of 106 respondents, 60 (57%) reported their child had obesity at the time of survey completion. In contrast, only 6 (5.7%) had obesity prior to craniopharyngioma diagnosis. A majority (92%) of those with obesity had tried limiting calories or carbohydrates; 31% and 69% found these helpful, respectively. Thirty-eight percent had tried weight loss medications (stimulants, metformin, GLP1R-agonists, and topiramate) and 48% found at least one helpful. Both stimulant and anti-depressant use were reported more frequently with obesity. An index (T-score) reflecting social function was lower in the cohort than a population reference, 41 (SD 11) vs. 50 (SD 10), p<0.001. In a linear model, both older age and obesity were independently associated with impaired social impairment. Ninety-four percent of respondents caring for a child with obesity (and 79% of all respondents) identified “improving treatments and prevention for hypothalamic obesity” as a key research priority. Conclusions: Only a minority of individuals with hypothalamic obesity had trialed medication, even though many reported that lifestyle modification was inadequate. Furthermore, social function was significantly impaired overall in survivors compared to a reference cohort, and even more so in individuals with obesity. These findings highlight the opportunity to improve social functioning as an additional potential benefit of improved treatments for hypothalamic obesity.